Methodology issues of forensic excavations at coastal sites. The Cyprus (Committee on the Missing Persons in Cyprus) experience. - Ktori, Maria; Moyssi, Noly; Kahraman, Deniz; Korkmaz, Evren (Journal of Greek Archaeology, 2016)
In 1981, the talks between the Turkish Cypriot and Greek Cypriot leaders resulted in the establishment of the Committee on Missing Persons in Cyprus (CMP), as a tripartite bi-communal committee taking decisions on the basis of consensus. It is comprised of three Members, representing the Greek Cypriot community, the Turkish Cypriot community, while the Third Member is nominated by the International Committee of the Red Cross (ICRC) and appointed by the United Nations Secretary-General.